Dislocation Following Total Hip Arthroplasty: An Overview of Contributing Factors. Issue 1 (January 2017) - Cunningham, Robert; Beck, David; Peterson, Chad
Abstract : Dislocation is one of the major postoperative complications following total hip arthroplasty (THA), with a prevalence of up to 7% in patients who have undergone primary THA. Dislocation has been shown to be associated with increased mortality rates and increased costs of care; therefore, minimizing the risk of dislocation is crucial in order to provide the best possible outcome for patients. There are numerous factors that have been associated with dislocation following THA. This article provides an overview of those factors to guide providers to minimize the risk of dislocation as a postoperative complication.